An In Vitro Study on Extracellular Vesicles From Adipose-Derived Mesenchymal Stem Cells in Protecting Stress Urinary Incontinence Through MicroRNA-93/F3 Axis - Wang, Lu; Wang, Yali; Xiang, Yuancui; Ma, Jinping; Zhang, Hui; Dai, Jingfang; Hou, Yanan; Yang, Yupei; Ma, Jingru; Li, Hongjuan (Frontiers in Endocrinology, 2021)
Since the potential roles of extracellular vesicles secreted by adipose-derived mesenchymal stem cells (ADSCs) is not well understood in collagen metabolism, the purpose of this research was to evaluate the effects of ADSCs-extracellular vesicles in stress urinary incontinence and the regulatory mechanism of delivered microRNA-93 (miR-93). ADSCs were isolated and cultured, and ADSCs-extracellular vesicles were extracted and identified. Stress urinary incontinence primary fibroblasts or satellite cells were treated with ADSCs-extracellular vesicles to detect the expression of Elastin, Collagen I and Collagen III in fibroblasts and Pax7 and MyoD in satellite cells. After transfecting ADSCs with miR-93 mimics or inhibitors, extracellular vesicles were isolated and treated with stress urinary incontinence primary fibroblasts or satellite cells to observe cell function changes. The online prediction and luciferase activity assay confirmed the targeting relationship between miR-93 and coagulation factor III (F3). The rescue experiment verified the role of ADSCs-extracellular vesicles carrying miR-93 in stress urinary incontinence primary fibroblasts and satellite cells by targeting F3. ADSCs-extracellular vesicles treatment upregulated expression of Elastin, Collagen I and Collagen III in stress urinary incontinence primary fibroblasts and expression of Pax7 and MyoD in stress urinary incontinence primary satellite cells. miR-93 expression was increased in stress urinary incontinence primary fibroblasts or satellite cells treated with ADSCs-extracellular vesicles. Extracellular vesicles secreted by ADSCs could deliver miR-93 to fibroblasts, and then negatively regulate F3 expression; ADSCs-extracellular vesicles could reverse the effect of F3 on extracellular matrix remodeling in stress urinary incontinence fibroblasts. miR-93 expression was also increased in stress urinary incontinence primary satellite cells treated by ADSCs-extracellular vesicles. extracellular vesicles secreted by ADSCs were delivered to satellite cells through miR-93, which directly targeting F3 expression, and upregulating Pax7 and MyoD expression in satellite cells. Our study indicates that miR-93 delivered by ADSCs-extracellular vesicles could regulate extracellular matrix remodeling remodeling of stress urinary incontinence fibroblasts and promote activation of stress urinary incontinence satellite cells through targeting F3.